Hierarchical-metal–organic framework-templated Cu0.5Zn0.5In2S4-rGO-g-C3N4: flexible synthesis and enhanced photocatalytic activity. Issue 42 (20th October 2020) - Xu, Mei-Ling; Liu, Ling-Wang; Wang, Kai; Dou, Yi-Chuan; Li, Kui; Cheng, Xin; Zhang, Feng-Ming
Abstract : The g-C3 N4 -rGO nanosheets are uniformly inserted into hollow Cu0.5 Zn0.5 In2 S4 quaternary sulfide derived from ZnCu-MIM@In-PTA hierarchical-MOFs, which illustrates excellent photocatalytic hydrogen evolution rate even in pure water. Abstract : MOF-templated sulfides exhibit abundant active sites and excellent photo/electrocatalytic activity, while the types of sulfides derived from the single-ligand-MOF are limited due to the poor structure coordination between the required metals and a given single ligand. Herein, uniform-element-distributed hierarchical-MOFs (HMOFs) have been prepared using dual ligands, and were adopted for the fabrication of uniform quaternary hollow Cu0.5 Zn0.5 In2 S4 nanocrystals. The uniform insertion of g-C3 N4 and g-C3 N4 -rGO into the skeleton of the hollow Cu0.5 Zn0.5 In2 S4 improved the photocatalytic hydrogen activity by 3.3 and 5.6 times in comparison with that of the optimal hollow Cu0.5 Zn0.5 In2 S4, due to the improved separation and transport efficiency of charge carriers. Notably, even in pure water, the hollow Cu0.5 Zn0.5 In2 S4 and its heterostructures exhibited considerable H2 and H2 O2 production activity. This work provides insight into the design and flexible synthesis of various MOF-templated nanocrystals for energy conversion and storage.